ILRI 40 years: Healthy animals equals healthy, productive people - Babiuk, L.A. (International Livestock Research Institute, 2014)
Feature address by Lorne Babiuk at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives. ILRI@40 conference, Addis Ababa, Ethiopia, 6–7 November 2014.